The Effect of Third-Party Funds (TPF) and Loan to Deposit Ratio (LDR) on Net Interest Margin (NIM) at PT Danamon Indonesia Tbk. - Nurul Hikmah; Nafisah Nurul Rahmatir; Juwani Juwani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of Third-Party Funds (TPF) and Loan to Deposit Ratio (LDR) on Net Interest Margin (NIM) at PT Bank Danamon Indonesia Tbk. A quantitative approach with multiple linear regression was employed using annual financial reports for the period 2019–2023. Classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that TPF has a positive and significant effect on NIM, while LDR does not have a significant effect. However, simultaneously, TPF and LDR significantly influence NIM with a coefficient of determination (R²) of 78.6%, indicating that most variations in NIM can be explained by these two variables. These findings emphasize the dominant role of TPF mobilization in enhancing bank profitability.